Portrayal of Women in Indian Tamil Films Directed by Women: A Feministic Reading - Raguram, S.; Poongulaly, S. (5th International Conference on Social Sciences 2018 (ICOSS 2018), 2018)
The world we live in is clearly permeated with media. Films are the twentieth century’s definitive medium of mass communication. In that powerful medium, the representation of women in films is highly complex and popular on movies and is increasingly more demands. The women portrayal continues in local cinema with other formulas throughout the history. The aim of this study is to determine the portrayal of women representation in Indian Tamil films; which were directed by women directors. The prime objective of this study is to analyse how the films of women directors having specific approaches on portrayal of women in their films. And, the secondary objective is to investigate significant differences between the men directors and women directors when they portray the women in their respective films. The sociological approach employs in this study through the feministic reading and three films which are recently directed by women are selected by the researcher as samples. The content analysis was used by the researcher in both qualitative and quantitative ways to find out the answer for the research questions: how women portrayed in Indian Tamil films, films were directed by women and how women directors handled gender issues in their films. The findings of the research exposed that the most part of the scenes portray the women as smart, energetic and able to make their own decisions and not in stereotypes. Further, the findings revealed that, even though, the women characters show the innocence, they become stronger when the male dominant society put pressures on them. While the male directors portray the women character as dependent largely, the women directors produce them not depending on anybody. On other side, the study made known that the portrayal of women in the scenes involve with physical affections and the exposure of female body were elaborated and illustrated in detail of the point of view of the women by female directors than male counterparts.
Keywords: Indian Tamil Cinema; Portrayal; Female Directors; Feministic Reading